2024
DOI: 10.1021/jacs.4c01047
|View full text |Cite
|
Sign up to set email alerts
|

4f/5d Hybridization Induced Single-Electron Delocalization in an Azide-Bridged Dicerium Complex

Yan Guo,
Xue-Lian Jiang,
Qun-Yan Wu
et al.

Abstract: Dilanthanide complexes with one-electron delocalization are important targets for understanding the specific 4f/5dbonding feature in lanthanide chemistry. Here, we report an isolable azide-bridged dicerium complex 3 [{(Trapen TMS )Ce} 2 (μ-N 3 )] • [Trapen = tris (2-aminobenzyl)amine; TMS = SiMe 3 ], which is synthesized by the reaction of tripodal ligand-supported (Trapen TMS )-Ce IV Cl complex 2 with NaN 3 . The structure and bonding nature of 3 are fully characterized by X-ray crystal diffraction analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Moreover, some related studies have shown that tripod ligands have advantages in the construction of fivecoordinate triangular bipyramidal complexes. [27][28][29][30][31][32] Inspired by previous work, we were interested in preparing a new class of five-coordinate triangular bipyramid mononuclear Dy III -based SIMs with local D 3h symmetry. For deeper understanding of magneto-structural correlation and detailed theoretical elucidations of the dynamic magnetic behaviors in five-coordinate Dy III SIMs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some related studies have shown that tripod ligands have advantages in the construction of fivecoordinate triangular bipyramidal complexes. [27][28][29][30][31][32] Inspired by previous work, we were interested in preparing a new class of five-coordinate triangular bipyramid mononuclear Dy III -based SIMs with local D 3h symmetry. For deeper understanding of magneto-structural correlation and detailed theoretical elucidations of the dynamic magnetic behaviors in five-coordinate Dy III SIMs.…”
Section: Introductionmentioning
confidence: 99%